CLINICAL EFFICACY AND SUBJECTIVE PAIN EVALUATION OF TWO ULTRASONIC SYSTEMS IN NON-SURGICAL PERIODONTAL TREATMENT OF MODERATELY ADVANCED CHRONIC PERIODONTITIS - Elena Firkova; Blagovesta Yaneva (Peytchinski Publishing, 2019)
Objective: To compare the clinical efficacy and perception of pain between VectorTM -system and a conventional P5 ultrasonic system in the non-surgical treatment of chronic periodontitis. Materials and methods: 45 patients with moderate periodontitis were treated by Vector™-system and a conventional P5 ultrasonic device in a split-mouth design clinical trial. At baseline and 6 weeks after non-surgical phase of treatment was completed, plaque index, bleeding on probing, pocket probing depth and clinical attachment levels were measured and recorded. A visual analogue scale was used to evaluate the patients' perceived pain immediately after scaling and root planning. Results: At 6 weeks of evaluation, all sites showed an improvement in clinical parameters. No statistically significant differences in pocket probing depth and bleeding on probing was observed between the groups. However the Vector™-system - treated group showed a greater improvement in reduction of pocket depth than P5 device. Patients treated with Vector™-system (mean=22.5 mm, SD=7.53 mm) experienced almost 80% less pain compared with the pain, experienced by the other conventional ultrasonic device (mean=37.16 mm, SD=11.30 mm). Conclusion: During initial periodontal treatment for the patients with moderate periodontitis, Vector™-system could achieve a comparable clinical efficacy in means of reduction of major clinical parameters and reduced pain sensation compared to the conventional ultrasonic device instrumentation.